Reactions of connective tissue to self-etching/priming dentin bonding systems: oxidative stress, tumor necrosis factor α expression, and tissue reactions - Yahya Orçun Zorba; Mehmet Yildiz; Abdulkadir Yildirim; Nesrin Gursan; Ertugrul Ercan (Elsevier, 2009)
Few data have been published concerning tissue and systemic responses to resinous dental materials. The aim of this study was to compare and evaluate the biocompatibility of four kinds of dental self-etching/priming adhesives by measuring tissue responses, local and systemic tumor necrosis factor (TNF) a expression, and oxidative stress parameters. Materials and methods: Eighty rats were equally divided into 10 groups. Four dental adhesives (Clearfil SE Bond, iBond, Clearfil Protect Bond, and Adper Prompt L-Pop) were applied to connective tissue of the rats. In the control group, rats were operated on with no material being applied. Biocompatibilities of the bonding agents were evaluated according to tissue responses, histopathologic and biochemical TNF-a expressions, and levels of malondialdehyde, glutathione, superoxide dismutase and glutathione peroxidase activities 1 week and 1 month after initiation of treatment. Results: All neutrophil levels and edema formation between the iBond group and the other groups were statistically significant after 1 week. Fibroblast levels in the Clearfil SE Bond group were higher than all other groups. Vascularization levels statistically differed between the Clearfil SE Bond and iBond groups, and between the Adper Prompt L-Pop and control groups. Tissue TNF-a levels statistically differed in all groups other than the control group. At the end of 1 month, the neutrophil level in the iBond group was higher than that in the control group. The differences in fibroblast levels after 1 month were statistically significant between the Clearfil SE Bond and Clearfil Protect Bond groups, and between the control and iBond groups. Tissue TNF-a levels were higher in the iBond, Clearfil Protect Bond, and Adper Prompt L-Pop groups than in the Clearfil SE Bond and control groups. Conclusion: There were no statistical differences in levels of serum TNF-a and oxidative stress parameters in any groups during the course of the study. The four different adhesive systems exhibited different degrees of local toxicity to the subsurface of the skin of rats, but no systemic toxicity was detected.